Exploring pandemic holiday practices: Meaning, experience and aspiration - Sara Skarp; Claire Hoolohan (Annals of Tourism Research Empirical Insights)
During Covid-19 holiday travel became shorter in distance and more surface-based, presenting an unusual opportunity to explore people's experiences of less carbon-intensive holiday travel. In this paper, survey and interview data are used to investigate pandemic holiday practices, exploring how meanings and aspirations relate to travel distance and mode. The findings illustrate the complexity of modal shift and air travel reductions. Despite showing that many people gained experience in surface-based travelling during Covid-19, we also show that what is a satisfying holiday experience can be achieved to differing degrees with short-distance or flight-free travel. Therefore, changing travel demand requires exploring how ‘proper’ holiday experiences could be provided domestically, and how shared ideas about what a holiday entails can be altered.